Coupling heat and mass transfer for determining individual diffusion coefficient of a hot C3H8–CO2 mixture in heavy oil under reservoir conditions. (November 2016) - Zheng, Sixu; Sun, Huijuan; Yang, Daoyong
Highlights: Heavy oil is characterized as multiple pseudocomponents, while BIP matrix is tuned. A two-dimensional heat and mass transfer model incorporating the PR EOS is developed. Individual diffusion coefficients for hot C3 H8 –CO2 –heavy oil systems are determined. A higher C3 H8 concentration accelerates diffusion and induces a stronger oil swelling. Abstract: By characterizing heavy oil as multiple pseudocomponents, a generalized methodology has been developed to determine both apparent and individual diffusion coefficients by coupling heat and mass transfer for hot C3 H8 –CO2 –heavy oil systems under reservoir conditions with consideration of swelling effect. Experimentally, a visualized PVT setup has been used to conduct diffusion tests for hot C3 H8 –CO2 –heavy oil systems with different C3 H8 concentrations under a constant pressure. The dynamic volume change of liquid-phase is monitored and recorded during the measurements. Theoretically, the volume-translated Peng–Robinson equation of state (PR EOS) with a modified alpha function has been incorporated to develop a two-dimensional heat and mass transfer model for the hot C3 H8 -enriched CO2 –heavy oil systems, while the heavy oil sample has been characterized as three pseudocomponents for accurately predicting phase behavior of the aforementioned systems. The binary interaction parameter (BIP) correlations are tuned with the experimentally measured saturation pressures, while the tuned BIPs are validated with the measured equilibrium swelling factors. Both the individual diffusion coefficient of each component and the apparent diffusion coefficients of C3 H8 –CO2 mixtures are determined once the discrepancy between the measured and calculated dynamic swelling factors of heavy oil has been minimized. Compared to CO2 alone, C3 H8 –CO2 mixtures lead to enhanced swelling effect of heavy oil, while a higher C3 H8 concentration achieves a faster dissolution and a larger dynamic swelling factor. Thus, C3 H8 preferentially diffuses into heavy oil than CO2 at the same conditions for C3 H8 –CO2 –heavy oil systems.